I have the following Expression:
ex = :(sum(x[i] for i=1:4)- y * y + z)
which I would like to evaluate over some data x, y, z. I have tried doing direct substitution through symbolic manipulations, but it is abysmally slow (~0.2s per set of substitutions).
It seems the right approach is to turn it into a function as here, but the application of that is somewhat limited.
Is there a method for converting
ex into a function like the following?
f(x,y,z) = sum(x[i] for i=1:4)- y * y + z
Thanks in advance!